THE CHANGING WORLD ORDER AFTER COVID-19 - ÜSTÜNDAĞ , Ceyda; SAĞIR, Dilan (SSD Journal, 2020)
Covid-19, which emerged in China and surrounded the world in a short time, it has become a serious threat. In addition to individual measures, governments and international organizations also have a serious responsibility to ensure the return of life to normal. . Since the epidemic has the potential to cause a transformation that can be felt in many areas for many years, its impact on global politics will be inevitable. The concept of "individual freedom" brought about by the liberal world order that has been going on for years has been replaced by the concept of "strong state" as a result of the intervention of states in many areas as a result of the global epidemic. Since the pandemic poses a great threat in the current period, it has become an international security issue. The ineffectiveness of global cooperation, the inability of international organizations such as the World Health Organization and the European Union to fulfill the roles expected from them, the inward-oriented policies of the US under Trump, which is described as the superpower of the multipolar system, push the states to loneliness and put the struggle alone and competition between states and It also prepares the ground for the environment of conflict. Although he fact that China is seen as more successful in limiting the epidemic in the country compared to other countries led to be asked “Can authoritarian regimes rise?”, when the struggle of democratic countries against coronavirus is examined, it is seen that the main issue is "manageability". One of the important issues affecting the coronavirus combat performance of states is their potential to effectively continue crisis management. In addition to ensuring the legitimacy of governments in the eyes of the people, this issue has also become the determinant of the power factor in the international community. It is seen that governments that cannot manage the crisis effectively, in the process of combating the epidemic, take a more aggressive attitude by throwing diplomacy and compromise in the international arena. Many countries already affected by the virus are struggling in many areas such as food security, health system investments, digital security, border problems, economic problems and trying to develop applicable policies in the "new order". As it is known, with the globalization that started to take effect from the beginning of the 1990s, a world order in which borders became flexible and individuals, capital and services freely moved was adopted. With the Covid-19 pandemic, a new one has been added to the problems caused by globalization and the efforts of the state and organizations to produce global solutions have begun to be questioned. In this study, the effect of Covid-19 on the internal and external relations of countries, management understanding and mutual attitudes of countries will be examined.